Implementing a teleophthalmology referral platform in routine practice: Understanding a digital health intervention implementation using normalisation process theory - Sarah Abdi; Dilisha Patel; Josie Carmichael; Konstantinos Balaskas; Ann Blandford (Digital Health)
Objective Digital health interventions have the potential to improve clinical processes and patient outcomes ; however, many face challenges during the adoption and implementation stages, hindering their overall impact. Our study uses normalisation process theory (NPT) as a theoretical approach to explore the facilitators and barriers to the implementation of a teleophthalmology referral platform in the United Kingdom, as an illustrative case of the implementation of a digital health intervention in routine practice. Methods Semistructured interviews were conducted with 24 health professionals (18 optometrists and 6 ophthalmologists) involved in the implementation of a teleophthalmology referral platform. NPT guided data collection and analysis. Results Most participants were ready to engage with the teleophthalmology referral platform, recognising its potential value and benefits. However, during implementation, participants’ perceptions varied; a major factor was whether their expectations from the technology were met, particularly regarding the feedback from the secondary eye care component of the referral platform. Several additional factors were identified that would influence the adoption of the platform. These included individual aspects (e.g. participants’ IT skills), technology-related factors (e.g. the time required to complete referrals) and organisational factors (e.g. investment in community optometry services). Conclusions To successfully implement the teleophthalmology platform into routine practice, particularly on a large scale, multiple factors at different levels must be considered. This study highlights the complexity associated with implementing digital health interventions in routine practice and the contribution of NPT in untangling some of these complexities.